SISTEM PEMASARAN KARET RAKYAT DI PROVINSI JAMBI DENGAN PENDEKATAN STRUKTUR, PERILAKU, DAN KINERJA PASAR - Dwi Nurul Amalia; Rita Nurmalina; Amzul Rifin (Jurnal Tanaman Industri dan Penyegar, 2013)
Rubber is the main commodity of Jambi Province. In the rubber market, price volatilites at exporter level are not followed by price volatilities at farmer level. Generally the objectives of this research was to analyze the marketing system of rubber smallholders with structure-conduct-performance (SCP) approachment. The research was conducted on two district of rubber production centers in Jambi province from June to August 2013. The method used in this research is survey method with interview techniques. The research results show that market concentration ratio (CR4) at crumb rubber factory level is 75.70%. These structural characteristics indicate that market structure is concentrated with low competition level. Hence, market structure of rubber is oligopolistic and the main marketing intitution determining rubber prices is crumb rubber factory. Market conduct analysis states that marketing collution occurs crumb rubber factories determine the price. In addition, the market performance analysis shows that changes of rubber prices at the crumb rubber factory level are not transmitted to farmers. The result analysis of market performance indicates that farmers are the most disadvantages actors comparing with other marketing actors and they are also price taker in the short run and long run.